PWE-041 Retrospective Study of Patients with Microscopic Colitis. (June 2019) - Allen, Ruridh; Reid, Gordon; Salunke, Santosh
Abstract : Background: Microscopic colitis (MC) in its 2 histologically distinct patterns - Lymphocytic Colitis (LC) and Collagenous Colitis (CC)- is an increasingly common cause of non-bloody diarrhoea. There appears to be an association with other autoimmune conditions and a number of culprit medications such as selective serotonin reuptake inhibitors (SSRI) and proton pump inhibitors (PPI). There appears tobe a variability in patient journey from referral to treatment. Aim: We looked to assess the current referral process, demographics and management of patients with MC within Forth Valley Royal Hospital (FVRH). Method: We performed a retrospective analysis of all patients with histologically proven MC from December 2016-December 2017 in FVRH. Data was obtained from pathology reports and patient details, including all clinical data was collected using 'clinical portal'. Findings: In total data was collected from 55 patients, 41 of these were female, with a median age of 65. 36 patients had LC, 15 CC and 4 patients had a mixed or unclear diagnosis. Although 9 patients had a minor rise infaecal calprotectin of >200. None of these patients had othersignificant pathology such as inflammatory bowel disease or colonic cancer. Patients reported watery diarrhoea in 54 of 55 cases with weight loss and abdominal pain being described in 16 and 19 patients respectively. Average length of symptoms at time of diagnosis was 4.8 months. 43 patients were on at least one medication which is known to be associated with MC and of these medications were reviewed in 31 cases (72%) with culprit medications being stopped or changed in 16 patients (37%). In total 32 patients were commenced on therapy for their MC with 19 (59%) receiving a reducing course of Budesonide, 7 (22%) receiving a fixed dose of Budesonide and 6 (19%) receiving 5-ASA. All 55 patients were triaged to have 'direct-to-test' colonoscopy, however, only 12 patients (22%) were referred directly to gastroenterology from GP. In total 42 patients were referred to surgical specialties with 30 of these patients receiving onwards referral to gastroenterology, often via their GP which resulted in a delay of up to 12months in some patients. Only 5 patients had recurrent disease, with 2 patients undergoing active investigation at the time of data analysis. Conclusion: Our data set is in keeping with other published data on MC. There is a variation in both referral pathway and management of these patients in FVRH. There exists no common pathway and time taken to see a gastroenterologist is often lengthy and arduous. Review of culprit medications appears to be often overlooked and this may result in ongoing symptoms or recurrent disease. Within FVRH we are currently undertaking a service change with an aim to streamline the referral process, standardise management and improve the patient journey.